Exploration of Salinity Effect on Palyno-Morphological Characteristics of Plant Species Collected From Salt Range (Bangladesh Journal of Plant Taxonomy, 2024)
This study aims to explore the pollen morphology of 19 plant species from the Khewra Salt Range by using light microscopy (LM) and scanning electron microscopy (SEM). Plant specimens were collected from various sites in the Khewra Salt Range, identified, and deposited in the Herbarium of Pakistan. Pollen morphology was studied using LM and SEM. Quantitative characteristics, including polar and equatorial diameter, exine thickness, colpus and spines length and width were studied using LM. The studied pollen taxa exhibited extensive variation in size and sculpture, with potential taxonomic implications. Pollen shape of most of the studied species was sub-spheroidal but pollen sizes ranged from 0.98 µm to 14.3µm. Symmetry and polarity of pollen grains were observed, contributing to plant species identification. The P/E ratio varied from Dichanthium annulatum (0.56) to Medicago polymorpha (1.15). Scanning electron micrographs revealed diverse exine sculpturing patterns, such as scabrate and echinate. At the same time, Nerium oleander (0.7-2.1µm) showed high exine thickness and large size colpus with a length of 7.5µm and width of 8.26µm. The largest spines were observed in Vicia sativa (3.7µm long and 1.38 µm wide). The taxonomic key based on palyno-morphological characters offers a tool for quick and precise identification. Pollen viability values were determined. Highest pollen viability was noted for Capparis decidua (97%) that show the species adaptation in Salt range. Palynological features can aid in resolving taxonomic problems and contribute to further karyological and taxonomic evaluations. This study contributes valuable insights into the palynological diversity of plant species of salt range, emphasizing the importance of pollen morphology in understanding and conserving salt-affected ecosystems.Bangladesh J. Plant Taxon. 31(1): 33-49, 2024 (June)